The Potential of Turmeric Rhizome Extract in the Preparation of Cosmetic Creams and Lotions: A Systematic Literature Review - Daila Ardiswina Pondini; Eka Helmy Rosyadi; Ghofaro Nurul Azzahro; Irdiyani Fariha; Pitaloka, Lola; Muhammad Reza Akbar; Nia Yuniarsih (Eureka Herba Indonesia, 2023)
Turmeric (Curcuma longa) is one of the spices that have been used traditionally in medicine and beauty in various cultures for centuries. The utilization of turmeric rhizome as a cosmetic component lotion or cream is believed to be able to enhance the efficacy of these cosmetics. This study aimed to describe the potential of turmeric rhizome extract in cosmetic preparations and lotion. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of turmeric in cosmetics. The search was performed using the terms: (1) "turmeric" OR "turmeric" OR" Curcuma longa" OR "Curcuma domestica" OR" turmeric in cosmetic" AND (2) "Curcuma longa" OR "turmeric". A powerful antioxidant and anti-inflammatory, which can help fight signs of aging on the skin. The active compounds of curcumin in turmeric are anti-inflammatory, antimicrobial, and powerful antioxidants. The combination of these properties makes it an attractive choice for use in cosmetics a cream specifically designed for wound healing on the skin. Studies have shown that curcumin in turmeric can reduce sebum production by the sebaceous glands, reducing the likelihood of acne formation. In conclusion, turmeric rhizome extract has the potential to antiaging, wound healing, and anti-acne in cosmetics in the form of cream or lotion.